Documentation of Wild Edible Fruits in Palangka Raya City - Lestari, Ria Windi; Wahid, Muhammd Risman; Pataya, Muhammad Rizki (JURNAL BIOLOGICA SAMUDRA, 2025)
Kalimantan Island is one of the regions with high diversity of wild edible fruit plants that are utilized by both local and urban communities as food resources, particularly as sources of vitamins. This study aimed to document the diversity of local seasonal fruits traded in the urban area of Palangka Raya City. Data were collected through observation and recording at traditional markets, seasonal vendors, and online marketplaces (social media) in Palangka Raya City during the period from November 2022 to August 2024, with species identification based on morphological characteristics and verified using botanical literature and online plant databases. A total of 65 species of local seasonal fruits, belonging to 21 plant families and 35 genera, were documented. The results indicate that local seasonal fruits remain highly consumed and have considerable economic value during their fruiting seasons. The data generated in this study provide a baseline for the conservation of local seasonal fruits, the strengthening of local food security, and the monitoring of phenological dynamics and the impacts of climate change in urban areas.